Effectiveness Of Remote Working And Hybrid Working On Employee Productivity - Syamsulbari Syamsulbari; Ikhsan Ibrahim; Puti Mandasari; Ansar Ansar; Ali Badarudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Changes in work patterns in recent years have encouraged organizations to adopt flexible work arrangements, including remote working and hybrid working. These systems provide employees with greater flexibility in completing their tasks; however, their effectiveness in improving employee productivity remains an important concern. Employee productivity is influenced by various factors, including work flexibility, communication, technological support, work environment, time management, and collaboration with colleagues. This study aimed to analyze the effectiveness of remote working and hybrid working on employee productivity. A quantitative analytical study with a cross-sectional design was conducted among employees working under remote and hybrid work arrangements. The study involved 60 respondents selected using purposive sampling. Data were collected through structured questionnaires assessing work system effectiveness and employee productivity. Data analysis included univariate and bivariate analyses using the Chi-square test. The findings showed that 32 respondents (53.3%) worked under a hybrid working system, while 28 respondents (46.7%) worked remotely. High employee productivity was reported by 38 respondents (63.3%), whereas 22 respondents (36.7%) demonstrated low productivity. Employees working under the hybrid system exhibited a higher proportion of high productivity than those working remotely. Statistical analysis indicated a significant relationship between work arrangement and employee productivity (p < 0.05). These findings suggest that both remote working and hybrid working can support employee productivity when accompanied by effective communication, adequate technological support, clear work targets, and efficient time management. Nevertheless, hybrid working demonstrated a stronger tendency to enhance employee productivity compared with remote working, indicating that combining workplace flexibility with periodic in-person collaboration may provide greater benefits for organizational performance